Analysis of Implementation in Cash Budgeting to Facilities and Setting of the Residential Area in Public Housing Department (DPRKP) of Magelang District - Lazimatus Salamah; Ghina Fitri Ariesta Susilo (Journal of Contemporary Information Technology, Management, and Accounting, 2020)
The aim of this study is to analyze the application of the budget in the facilitation and structuring of residential areas at (DPRKP) in Magelang. This research uses qualitative methods. Interview and direct observation methods are used for getting the research data. The interview method was conducted with three informants from Dinas Perumahan Rakyat dan Kawasan Permukiman (DPRKP) of Magelang Regency. The results showed the process of preparing a saving budget in DPRKP for facilitation activities and structuring of residential areas in the Magelang Regency is using the implementation of a performance-based cash budget and guided by the Dokumen Pelaksanaan Anggaran (DPA).